The dual effects of iron deficiency on intervertebral disc development and on acute injury-induced disc degeneration - Hengrui Chang; Shaomeng Kang; Chenchen Li; Lihui Wu; Hongran Liu; Di Zhang; Yanzhong Chang (Scientific Reports)
Abstract Clinical studies have reported that anemic patients with lower back pain exhibit significantly more severe lumbar intervertebral disc (IVD) degeneration compared to non-anemic individuals. Given that iron deficiency (ID) is the leading cause of anemia, we hypothesized that ID may disrupt IVD metabolism—particularly extracellular matrix synthesis—thereby contributing to aberrant disc development and degeneration. To investigate this, we established an iron-deficiency anemia (IDA) rat model via an iron-deficient diet and induced IVD degeneration through needle puncture. Degenerative changes were assessed using MRI, while morphological alterations were evaluated via O-fast green and hematoxylin-eosin (H&E) staining. The gene expression was measured by quantitative reverse transcription PCR (RT-qPCR). Immunofluorescence staining was employed to observe the protein expression. Additionally, TUNEL (TdT-mediated dUTP nick end labeling) was performed to assess apoptosis in nucleus pulposus cells. Our findings revealed that iron deficiency significantly impaired the development of rat caudal intervertebral discs characterized by reduced MRI signal intensity, diminished notochordal cell populations in the nucleus pulposus, thinning of the cartilage endplate, and Impaired type II collagen synthesis. However, despite these developmental abnormalities, iron deficiency did not exacerbate puncture-induced disc degeneration. MRI and histological analyses showed no significant differences in degenerative severity between IDA and control groups following needle injury. Additionally, TUNEL assays indicated no marked increase in apoptotic activity in IDA rats.